Caracterización de la comunidad Ngöbe de Valle de Risco, Bocas del Toro, Panamá - Mendéz, Ernesto; Calvo, Gustavo; Ortíz, Meivis (CATIE, Turrialba (Costa Rica), 2020)
5 páginas, 1 figura, 3 tablas, 9 ref.